Crossbreeding with Africander dam as basis. 2. Weaning performance of progeny of various sire breeds - Mentz, A.H.; Els, D.L.; Coetzer, W.A. (1979)
Weaning mass was studied for 753 calves out of Africander cows by Africander, Brahman, Charolais, Hereford and Simmental sires. Crossbreds performed 11.1 per cent to 11.8 per cent better than Africander controls. Charolais progeny had a significantly greater weaning mass than Hereford and Simmentaler progeny with Brahman progeny in an intermediate position. When all cases of dystocia were taken into consideration, however, the net weaning mass output per cow calved for Simmental, Brahman and Hereford bulls was considerably better than that for Charolais and Africander bulls.